Insect Peroxiredoxins: A Comprehensive Review of Their Classification, Distribution, Structural Features, Expression Profiles and Physiological Functions - Li Yang; Shaohua Lu; Yujie Lu; Mingshun Chen; Sufen Cui (Insects, 2025)
With the development of technology, an increasing amount of literature regarding the expression profiles and physiological functions of Prxs has been published. Despite this growing interest, there is currently no systematic review of expression profiles in different insects. Here, we performed a systematic review of the available literature on the location and expression of Prxs in different tissues, developmental stages and sexes in insects. Recent studies on the structure, expression profiles and functional characterization of Prxs provide valuable insights into the molecular mechanisms and functional pathways of this important enzyme family. In insects, Prxs are crucial for antioxidant defense, development, stress adaptation, cell apoptosis, immune response and insecticide resistance. This systematic review provides an overview of the various functions of Prxs as reported in the literature and highlights that many environmental stresses induce changes in Prxs expression levels. Furthermore, we present perspectives on future research directions regarding insect Prxs and discuss their potential applications in pest control.